The effectiveness of mindful walking based on the timing it right framework in patients with atrial fibrillation and chronic heart failure - Qin Lu; Jingjing Lu; Yeping Zheng; Juanqin Shen; Xia Zhao; Jianjiang Xu; Xiaoping Gu; Zhenliang Chu (Frontiers in Cardiovascular Medicine)
ObjectiveTo explore the effects of mindful walking (MFW) based on the Timing It Right (TIR) framework on anxiety, depression, and cardiopulmonary function in patients with atrial fibrillation combined with chronic heart failure.MethodsA total of 86 patients with atrial fibrillation and chronic heart failure admitted to the cardiology department of our hospital between June 2023 and March 2024 were enrolled in this study. Two homogeneous management wards were selected, with 43 patients from Ward A serving as the control group and 43 patients from Ward B as the intervention group. After excluding those lost to follow-up or readmitted, 39 patients were included in the control group and 41 in the intervention group. The control group received routine care, discharge guidance, and exercise rehabilitation training, while the intervention group received MFW intervention based on the TIR framework in addition to the standard care treatment. The Five Facet Mindfulness Questionnaire (FFMQ), Self-Rating Anxiety Scale (SAS), Self-Rating Depression Scale (SDS), 6-minute Walk Distance (6MWD), incidence of adverse cardiac events, and Senior Fitness Test (SFT) were used for effect evaluation.ResultsThe observation period of the study was 24 weeks, and there were no significant differences in general information, pre-intervention SAS and SDS scores, FFMQ, 6MWD, and SFT between the two groups (all P > 0.05). Post-intervention, the SAS and SDS scores in the intervention group were 38.12 ± 4.18 and 37.34 ± 3.62, significantly lower than the control group scores of 54.05 ± 5.93 and 51.15 ± 5.91 (t = 13.938, 12.679, both P < 0.001). The intervention group's FFMQ scores for observing, describing, and acting with awareness were 25.98 ± 4.14, 28.68 ± 3.12, and 32.02 ± 3.49, all significantly higher than the control group's scores of 20.85 ± 3.31, 22.41 ± 1.94, and 26.82 ± 3.75 (t = −6.101, −10.735, −6.431, all P < 0.001). The 6MWD for the intervention group was greater than the control group (376.90 ± 42.99 vs. 312.13 ± 15.01, t = −8.904, P < 0.001). Additionally, the intervention group's lower limb muscle strength and grip strength were 11.00 ± 2.19 and 22.90 ± 3.94, both superior to the control group's 6.38 ± 2.54 and 16.85 ± 4.59, with significant differences (t = −8.715, −7.746, P < 0.001).ConclusionIn patients with atrial fibrillation and chronic heart failure, the Timing It Right-based mindful walking intervention group demonstrated significant improvements in mindfulness capacity, cardiopulmonary performance metrics, and negative emotion scores compared to standard care controls.